Phantom kidney at angionephroscintigraphy - S. P. Mironov; V. B. Sergienko; O. Yu. Narusov; D. N. Shul’gin (Вестник рентгенологии и радиологии)
Based on the analysis of the data available in the literature and own clinical observations, the authors consider the diagnostic value of the little known scintigraphic phantom kidneyphenomenon, a vascular pool that is detected at the angiographic stage of 99mТс-DTPA dynamic renal scintigraphy and that mimics a removed or absent kidney. The paper  describes two cases of the phantom kidney. In one case, the phantom kidneydetected on the side of nephrectomy manifested a kidney cancer recurrence in the bed of the removed organ; in the other, the kidney-like vascular pool in the patient with left-sided pelvic dystopic kidney was due to the recording of the intestinal vasculature at the site of the expected kidney location. Adherence to a number of methodical conditions for  conducting a study, as well as combined single-photon emission computed tomography/computed tomography examination will be able to avoid interpretation errors and to ensure an adequate further diagnostic algorithm.